Homicidas juveniles en Bogotá, estudio de grupos focales - Escobar Córdoba, Franklin (2015)
Background. Violence has been declared as a public health problem in the world. In the last years, there has been an alarming increase of the violence caused by adolescents. This has been reflected in several indicators as the number of homicides. Adolescents are both criminals and victims of many of these violent acts. Colombia has not escaped this phenomenon —being homicide its main way of violent death— and there is little specific data on juvenile homicidal population. Objective. To explore likely risk factors linked to homicide committed by two young populations: a schooled one and non-schooled one. Materials and methods. A qualitative study of two focus groups: one composed by young murderers and another by young non-murderers. Results. Studies show that the main risk factor is the access to and the use of weapons. Other risk factors affect the young’s murder disposition to develop a criminal behaviour and the control strategies chosen by them. Such factors are interpreted in different ways by young murderers and non-murderers. Conclusions. This study gives important data which can be used in order to design and establish strategies to handle juvenile murder as a public health issue.